Pre-treatment drug resistance among patients initiating antiretroviral therapy (ART) in Zimbabwe: 2008–2010. (December 2016) - Mungati, More; Mhangara, Mutsa; Gonese, Elizabeth; Mugurungi, Owen; Dzangare, Janet; Ngwende, Stella; Musasa, Patience; Wellington, Maureen; Shambira, Gerald; Apollo, Tsitsilina; Yang, Chunfu; DeVos, Joshua; et al.
Abstract Background Zimbabwe set up 12 sentinel sites to monitor HIV drug resistance (HIVDR) following the international standards for prevention of HIVDR from 2008 to 2010. Methods Participants were consecutively enrolled. Blood was collected and used for CD4 count, viral load (VL) and pre-treatment DR (PDR) tests besides routine baseline tests. We analyzed the characteristics of participants enrolled into the survey and estimated the point prevalence of PDR and its associated factors among ART initiators in a cross-sectional analysis using the baseline data collected from a prospective cohort in 12 purposefully selected sentinel sites. Results A total of 1728 participants (96 % response rate) were enrolled and 1610 had complete data. Of the 1610 there were more females (68.7 %) than males (31.3 %). The median CD4 count was 168 cells/mm3 with males having lower values (P = 0.003). Ninety-six percent of participants had a VL ≥ 1000 copies/ml and the median VL was 128, 000. Previous exposure to antiretroviral drugs (ARVs) was mainly through PMTCT (5 % of the participants). Overall, PDR mutations were detected in 6.3 % (95 % CI 5.2–7.7) of the 1480 successfully genotyped participants. However, the prevalence of PDR mutations was double for those with previous exposure (12.1 %) to ARVs compared with those without previous exposure (5.7 %, P = 0.002). Conclusions The results show a moderate level of PDR prevalence among ART initiators. To maintain the efficacy of the current first-line regimens, there is need to strengthen all HIVDR prevention efforts and to conduct further studies to investigate optimal strategies that can prolong the efficacy of first-line ARV regimens in the country.